Victor Hugo’s Idea on the Education and Formation System - Dilokwuthisith, Preecha (Saengtham College Journal, 2025)
Victor Hugo, one of France’s greatest writers, once said: “opening one school is equivalent to closing one prison”. However, there are still a large number of prisons today and they are increasing in number every year. The education system in France and in most other countries has been congruent with the industrial culture i.e. it aims to produce a large amount of products by using the same mould. In fact, educators or teachers should focus their attention rather, on the individual differences of their capabilities and talents as best as possible. Additionally, teachers should place stress on the formation of good habits e.g. loving kindness, good working habits, creativity, and a strong desire for the acquisition of knowledge. Above all, an appropriate education system should not stress only theoretical study or rote learning, but focus on the application of theory to real situations. In line with this, teachers should change the style of examinations away from evaluation of the memorization skills of students to the evaluation of their thinking skills, including their attitudes and personalities. In short, a good education system should aim at the development of productive manpower and adults endowed with loving kindness.